Access to and Control over Household Resources: A Consistency Check Using Gender Analysis and Household Survey Data (Nepal Agriculture Research Journal, 2009)
A study was conducted during 1998 covering three Village Development Committees (VDCs) ofChitwan district, Nepal, to examine the consistency of results if carried out independently usingformal and informal methods of information collection. Gender analysis (access and controlprofiles), and a face-to-face household survey (n = 123 households) were employed for thispurpose. Gender differences in access to and control over household resources was studied.Results showed a consistent response from both household survey and gender analysis for mostof the parameters studied, such as access to agriculture extension and veterinary services,participation in training, and community work. Gender response for control over resources, suchas income from small animals was also similar from both methods. However, some of theparameters were not consistent in response. For example, there was no participation of women incontrol over income from cash crops and cereal crops and large animals as strongly indicated bygender analysis, which was not visible in the case of household survey. This raises a questionabout the reliability of using only one approach of information collection for rural developmentresearch. On the basis of these results, we suggest a combine approach of quantitative andqualitative methods of data collection, which could be more reliable, informative andappropriate. The use of multiple methods also allows the researcher to cross-reference in order tovalidate the trustworthiness of information.Key words: Gender analysis; household survey; triangulationDOI: 10.3126/narj.v7i0.1875Nepal Agriculture Research Journal Vol.7 2006 pp.98-102